Analysis of foreign direct investment as a comparison of macroeconomic factors in seven countries Asean 5, China and Japan during period 1996-2015 - Aribowo, Wira Ganet (Journal of Economic Development, Environment and People, 2018)
The purpose of this research is to analyse the Determination of Foreign Direct Investment (FDI) As a Comparison of Macroeconomic Factors in Asean 5, China and Japan. Besides, this research also analyses the influence of macroeconomic factors due to the strength of the influence of macroeconomic factors to the shock. This research uses the secondary data during the period of 1996-2015 by using the Panel Data model. The variabel which is used here is the macroeconomic factor (Broad Money, Economic Development, labor force, exchange rate, industry, transport service) that has an affect on Foreign Direct Investment in Asean 5, China and Japan. The gap of this research is to connect the macroeconomic factor (Broad Money, Economic Development, labor force, exchange rate, industry, transport service) that has an affect on Foreign Direct Investment. The result of the research shows that the macroeconomic factors have positive effect in ASEAN 5 countries, China and Japan as Home Country, as well as Host Country. Meanwhile, the FDI has a negative impact from one of the macroeconomic factors that is ‘exchange rate’. The policy implication of this research is to suggest the monetary authority, government or private, to supervise the direct investment flow that enters the host countries.